2020
DOI: 10.1101/2020.04.13.20064006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic profiling of Italian patients identified methylation sites associated with hereditary Transthyretin amyloidosis

Abstract: Hereditary Transthyretin (TTR) Amyloidosis (hATTR) is a rare life-threatening disorder caused by amyloidogenic coding mutations located in TTR gene. To understand the high phenotypic variability observed among carriers of TTR disease-causing mutations, we conducted an epigenome-wide association study (EWAS) assessing more than 700,000 methylation sites and testing i) TTR coding mutation carriers vs. non-carriers, and ii) Val30Met (rs28933979) carriers vs. carriers of other TTR mutations. In the first analysis,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…This term was reported in the study of prefrontal gene expression patterns in rats by Duggan et al [42] In addition, only one intersection was found between iREAD and DEXSeq, which is neuron projection organization (GO: 0106027). This term was reported in the study on the interaction between AD and the Beta-secretase 2 gene [43] . The top 10 enriched GO terms of each method are shown in Fig.…”
Section: Differential Analysismentioning
confidence: 99%
“…This term was reported in the study of prefrontal gene expression patterns in rats by Duggan et al [42] In addition, only one intersection was found between iREAD and DEXSeq, which is neuron projection organization (GO: 0106027). This term was reported in the study on the interaction between AD and the Beta-secretase 2 gene [43] . The top 10 enriched GO terms of each method are shown in Fig.…”
Section: Differential Analysismentioning
confidence: 99%
“…Similarly, transcriptomic regulation appears to have a role in the onset of ATTRwt in non-carriers [20,21]. Other non-coding regulatory mechanisms such as epigenetic changes seem to affect ATTR genotype-phenotype correlation [22,23].…”
Section: Introductionmentioning
confidence: 99%